Linguistic attitudes towards Quechua speakers at the National University of San Marcos - Sullón Rios, Angela (2019)
The present study reveals the linguistic activities indicated by the students of the National University of San Marcos towards the Quechua speakers of that university. The objective of this article is to analyze the assessment that UNMSM students have towards the language and its speakers. For the development of this article, we work with a non-probabilistic sample where a questionnaire was applied that measures the statements through the Likert scale to 20 students, one from each faculty. The research concludes that students show positive linguistic attitudes towards Quechua in the academic context.